To Couple or not to Couple? For Acute:Chronic Workload Ratios and Injury Risk, Does it Really Matter? - Gabbett, Tim J.; Hulin, Billy; Blanch, Peter; Chapman, Paul; Bailey, David (International Journal of Sports Medicine, 2019)
We examined the association between coupled and uncoupled acute:chronic workload ratios (ACWR) and injury risk in a cohort of 28 elite cricket fast bowlers (mean±SD age, 26±5 yr). Workloads were estimated using the session rating of perceived exertion (session-RPE). Coupled ACWRs were calculated using a 1-week acute workload and 4-week chronic workload (acute workload was included in the chronic workload calculation), whereas uncoupled ACWRs used the most recent 1-week acute workload and the prior 3-week chronic workload (acute workload was not included in the chronic workload calculation). A nearly perfect relationship (R2=0.99) was found between coupled and uncoupled ACWRs. Using a percentile rank method, no significant differences in injury risk were found between the coupled and uncoupled ACWR. Higher ACWRs were associated with increased injury likelihood for both coupled and uncoupled methods, however there were no significant differences in injury risk between coupled and uncoupled ACWRs. Our data demonstrates that both coupled and uncoupled ACWRs produce the same injury likelihoods. Furthermore, our results are consistent with previous studies: higher ACWRs are associated with greater risk, irrespective of whether acute and chronic workloads are coupled or uncoupled.
Keywords: workload; load management; injury likelihood